Serverless Computing: Architecture, Challenges, and Future Trends - Thapliyal, Numa M.; Kumar, Pradeep; chandan, Manav (International Journal of Psychosocial Rehabilitation, 2020)
Serverless computing, a paradigm shift in cloud computing, has received prominence for its specific architecture, imparting benefits in terms of cost performance, scalability, and simplified deployment models. This studies provides an in-depth exploration of serverless computing, analyzing its structure, figuring out challenges, and envisioning future traits to enhance overall performance, scalability, and useful resource management. The structure of serverless computing is characterized with the aid of its event-pushed model, where capabilities are executed in response to specific events with out the need for provisioning or handling servers. This abstraction of infrastructure intricacies lets in developers to recognition totally on code, thereby streamlining the development procedure. The research delves into the additives of serverless architecture, emphasizing its capability for stepped forward agility and aid optimization. Despite its merits, serverless computing gives challenges that warrant careful consideration. Issues together with bloodless start latency, confined execution time, and the intricacies of managing stateless capabilities pose hurdles to its seamless adoption. This research significantly assesses those demanding situations, offering insights into potential answers and mitigations to decorate the overall efficiency and effectiveness of serverless deployments. An evaluation of the modern nation of serverless computing adoption exhibits its growing occurrence throughout various industries. Organizations are leveraging serverless platforms for obligations ranging from microservices deployment to facts processing. The research synthesizes cutting-edge adoption traits, highlighting successful use cases and areas wherein serverless computing demonstrates most impact. Looking forward, the research outlines destiny traits and enhancements to in addition solidify serverless computing as a transformative paradigm. The consciousness extends to improving performance thru optimizations in feature execution and lowering bloodless start latencies. Scalability enhancements, which include greater flexible aid allocation and control, are emphasised. Additionally, the research explores advancements inside the orchestration of serverless workflows and improved assist for stateful capabilities. In conclusion, this research offers a comprehensive knowledge of serverless computing, its architecture, and the challenges it presents. By analyzing the contemporary kingdom of adoption and proposing future developments, the examine aims to guide the evolution of serverless computing closer to stepped forward overall performance, scalability, and aid control, paving the manner for its persevered integration into diverse application landscapes.